Jogos eletrônicos e as memórias do trauma: reflexões sobre Death Stranding e The Last of Us Part II - Cristina Horta de Almeida (2022)
This study proposes to reflect on a possible relationship between electronic games and the forms of memory, a work that began in 2015 in the master's program. After a discussion from the perspective of cultural memory, the concept of post-apocalypse and the concept of post-human, now the proposed focus is the scenario of the memory of trauma and the provisional condition of humanity in the face of death, issues as an integral part of some game narratives. In addition to thinking about technology, the research turned to people, their relationships and existence, which in itself is traumatic. Here will be given a special attention to human relationship to time and how electronic games are able to turn interactive narratives into potential resources to produce memories. Thus, fundamentally, the research is supported by three foundations: narrative, trauma and memory. A theoretical framework is used based on some contributions from researchers such as Paul Ricoeur (1983/2020), who thought of narrative as a way of dealing with time; Janet H. Murray (2003), who worked with the notion of multiform entanglements in cyberspace; Marie-Laure Ryan (2001), who dedicated herself to the poetics of immersion and its aspect of preventing a return to the surface; Sigmund Freud (1900-1933/2010-2019) and Sándor Ferenczi (1931-1934/1992), who treated trauma and the psyche; Cathy Caruth (1996), who addressed the trauma literature; Dori Laub and Nanette Auerhahn (2017), who organized trauma memories in eight ways; Philippe Ariès (1977/2014), who made reflections about death. With a conceptual base built by these authors, a bridge was made between language studies (narrative) and psychoanalysis (trauma) to, then, go through the universe of electronic games, focusing on the possibility of a memory construction from of the contexts about death in Death Stranding (2019) and The Last of Us Part II (2020), both originally released for the PlayStation 4 console. We will analyze how these games can relate to the notions of affection and traumatic memory, without losing sight of considering the dialogue between scientific knowledge and everything that crosses the experience in the research. The study proves to be significant for the scientific and cultural development, and the ways of building memory from games.